Fabrication and evaluation of Ni/WSn solder joints for die-attach technology - Foo, Terry Zhi Yuan (Nanyang Technological University, 2022)
Micro electrical mechanical systems (MEMS) are very small integrated mechanical and electrical devices which are assembled via soldering of the individual components. For MEMS that operate at high temperatures, such solder materials are conventionally high lead content alloys, which is detrimental for the environment and personal safety. This report investigates using Transient Liquid Phase (TLP) bonding, instead of a conventional solder, with a nickel-tungsten-tin filler as an interlayer material with a varying percentage composition of tungsten to overcome this limitation. The joint consists of a heat-treated filler of tin foil sandwiched by nickel-tungsten electroplated layers. Differing tungsten atomic percentages in the nickel-tungsten thin films were used in the TLP process. The foil and layers were then pressed in a mold at 0.625 MPa at 300 °C for two hours before final cooling at room temperature. Mechanical stability and resilience of the TLP bond was assessed by evaluating shear strength and carrying out fracture profile analysis using a scanning electron microscope (SEM). The average shear strength ranged from 13.10 – 23.03 MPa which is significantly higher than the minimum requirement of 5 MPa for MEMS and also exceeded the MIL STD 883 standard. Fracture profile analysis indicated that cohesive failure occurred at the Ni3Sn4 intermetallic layer of the joint. These results suggest that a nickel-tungsten-tin TLP bond is a viable and promising candidate as a lead-free alternative to conventional solder material for use in MEMS.